Pengaruh Karakteristik Pemerintah Daerah Terhadap Kinerja Keuangan Pemerintah Daerah (Studi Empiris Pada Kabupaten/Kota Se-Jawa Tengah) - Abdillah, Yuni; , Dra. Nursiam, M.H., Ak., CA (2016)
This study aims to analyze the characteristics of the Local Government Influence on the Performance of Local Government Finance ( Empirical Study In District / City Central Java) . This study aims to determine how much influence the characteristics of local governments on the financial performance of local governments . This study examines the regional Government Financial Statements by taking samples of the 70 districts / cities in Java years 2012 /2013 . The data used in this research is secondary data . The analytical tool used in this research is multiple linear regression . The population in this study are all districts / cities in Central Java province in the year 2012/2013 . using saturated sample . Analysis of the data used in this study is the classical assumption test and test hypotheses using multiple regression analysis . The results of this study indicate that the size of the effect on performance of Local Government Local \ overnment Finance District / City of Central Java province in 2012-2013, Prosperity affect the financial performance District Government / City of Central Java province in 2012-2013, the legislative measure has no effect on performance Local Government financial District / City of Central Java province in 2012-2013. While eintergovernmental revenue do not affect the Financial Performance of the District Government / City of Central Java province in 2012-2013. keyword: financial performance , characteristics , size of government , prosperity , the size of the legislature , Intergovermental revenue.